Correlation between levels of physical activity, disease severity and pain intensity in women with fibromyalgia - Márcio Bruning; Jonato Prestes; Nuno Manuel Frade de Sousa; Gabriel Caetano Pereira; Fernanda Maria Borghi; Leonardo Pestillo de Oliveira (BrJP)
BACKGROUND AND OBJECTIVES: Currently, there is conflicting evidence regarding both physical activity and exercise in relation to the impact of fibromyalgia (FM). The aim of this study was to correlate levels of physical activity, disease severity, and pain in women with FM. METHODS: This is a cross-sectional study with 93 women diagnosed with FM, with an average age of 49.1±10.3 years. The Revised Fibromyalgia Impact Questionnaire (FIQR) was used to assess the impact of the disease on the women’s health status. To evaluate the level of physical activity, the short version of the International Physical Activity Questionnaire (IPAQ) was used. The Numeric Pain Rating Scale (NPRS) was used to assess the intensity of the participants’ pain. RESULTS: Significant differences were found between the groups in terms of symptom severity (F = 9.471; p<0.001; n2=0.174) and pain intensity (F = 5.074; p=0.008; n2=0.101), which were unfavorable to the sedentary group (p<0.05). Significant inverse correlations were found in assessments of physical activity levels at light and moderate intensities, FIQR and pain (rs = -0.20 to -0.30). CONCLUSION: Sedentary women are severely impacted by the disease and may experience higher levels of pain. Weak to moderate correlations between physical activity levels, disease impact, and pain intensity suggest that engaging in physical activity at light and moderate intensities may be an important intervention in the management of FM.